Hydrogen charging effects on the alternation of oxide film formed on Ni, Cr and Alloy 690 in high-temperature water. (December 2022) - Xu, Jian; Nong, Jing; Liang, Fengrui; Yuan, Sui; Ren, Lu; Guo, Qi; Shoji, Tetsuo
Abstract: The effects of hydrogen charging on the oxide film of Ni, Cr and Alloy 690 in high-temperature water were studied. Hydrogen was charged to the specimen during experiments. The inner layer of Cr exhibited amorphization after the hydrogen charging. The oxide film became thinner for Ni after hydrogen charging, and lots of cavities were observed along the boundary of inner oxide and matrix. The oxide film of Alloy 690 exhibited a mixed feature of Ni and Cr. The hydrogen diffusing to the solution not only affected the thermal stability of the oxide but also hindered the precipitation of outer oxide. Highlights: A dual-layer structure oxide was formed regardless of hydrogen charging. Generally, the hydrogen charging did not change the lattice structure. The hydrogen charging reduced the oxide thickness to different degrees. DH affected oxide stability and hindered outer oxide precipitation/deposition.